Complement regulatory protein genes in channel catfish and their involvement in disease defense response. Issue 1 (November 2015) - Jiang, Chen; Zhang, Jiaren; Yao, Jun; Liu, Shikai; Li, Yun; Song, Lin; Li, Chao; Wang, Xiaozhu; Liu, Zhanjiang
Abstract: Complement system is one of the most important defense systems of innate immunity, which plays a crucial role in disease defense responses in channel catfish. However, inappropriate and excessive complement activation could lead to potential damage to the host cells. Therefore the complement system is controlled by a set of complement regulatory proteins to allow normal defensive functions, but prevent hazardous complement activation to host tissues. In this study, we identified nine complement regulatory protein genes from the channel catfish genome. Phylogenetic and syntenic analyses were conducted to determine their orthology relationships, supporting their correct annotation and potential functional inferences. The expression profiles of the complement regulatory protein genes were determined in channel catfish healthy tissues and after infection with the two main bacterial pathogens, Edwardsiella ictaluri and Flavobacterium columnare . The vast majority of complement regulatory protein genes were significantly regulated after bacterial infections, but interestingly were generally up-regulated after E. ictaluri infection while mostly down-regulated after F. columnare infection, suggesting a pathogen-specific pattern of regulation. Collectively, these findings suggested that complement regulatory protein genes may play complex roles in the host immune responses to bacterial pathogens in channel catfish. Highlights: Nine complement regulatory protein genes were identified in channel catfish. Correct annotations were established by phylogenetic and syntenic analyses. Distinct expression patterns were observed between two bacterial infections.